1998
DOI: 10.1080/152279598308038
|View full text |Cite
|
Sign up to set email alerts
|

The Colostrum-Deprived, Artificially Reared Neonatal Pig as a Model Animal for Studying Rotavirus Gastroenteritis

Abstract: g astroenteritis is one of the main causes of acute diarrhea in young humans and animals u Rotavirus worldwide. T he colostrum-deprived, arti cially rear ed neonatal pig has been extensively used in our laborat ory as a model animal for studying an exper imentally induced rotaviral g astroenteritis. D etails on procurement of new born pig s, immunolog ic characteristics, and arti cial rearing conditions of colostrumdeprived neonatal pig s as well as on rotavirus inoculation, clinical manifestations, and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The piglets were fed a commercial pig milk replacer d based on a previously described regimen. 7 Intervals between feeding and observations of the piglets were never longer than 4 hr. The piglets were handled in accordance with the guidelines set forward in The Guide to the Care and Use of Experimental Animals of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 98%
“…The piglets were fed a commercial pig milk replacer d based on a previously described regimen. 7 Intervals between feeding and observations of the piglets were never longer than 4 hr. The piglets were handled in accordance with the guidelines set forward in The Guide to the Care and Use of Experimental Animals of the Canadian Council on Animal Care.…”
Section: Methodsmentioning
confidence: 98%
“…Protocols used for rearing of CD pigs as a newborn infant model for studying immune responses [ 10 , 11 ] or neurological development [ 12 ] have been recently described. Although several manuscripts report the use of CD pigs for study of infectious pathogens, few detail the rearing conditions [ 1 , 5 , 13 , 14 ]. Rearing protocols for CD piglets with limited or no use of antibiotics and more intensive feeding schedules have been previously described [ 1 , 5 ] and would be more appropriate for bacterial challenge studies.…”
Section: Pig Maintenance During the Trial Periodmentioning
confidence: 99%
“…In vivo evaluation using RV‐induced diarrhea animal models has provided key insights to understanding the pathogenesis of RVs and evaluation of the immune response of IRV. Studies have shown that cow, germ‐free pigs, rabbits, rats, and suckling mice can be induced into diarrhea models and used to study the RV infection, pathology, immune response, and vaccine efficacy . The immune mechanisms involved in the clearance of and immunity to RV infection need to be uncovered.…”
Section: Introductionmentioning
confidence: 99%